Evaluating the Performance of Albanian Savings and Credit (ASC) Union - Shore, Eralda; Nikolla, Mariana (European Journal of Sustainable Development, 2013)
This research paper aimed to evaluate the role of ASC Union through three main poles:its performance in relation to outreach, its financial sustainability, and its welfare impact.It was based mainly on a descriptive study and focused on an accurate event, trying toanswer questions such as: what, where, how, who and when, through the use of differentinformation and already existing theories. Moreover, a triangulated methodologycombining interviews, questionnaires and observations was applied in order to analyze themicrocredit impacts.From the outreach angle, it was found that ASC Union's outreach has shown anincrement over the period of study with different rates of growth from 2003 to 2010 onaverage by 14.7%. On the other hand, the operational sustainability measured by returnon assets and return on equity showed instability over the period of the study, making theASC Union financial sustainability doubtful. In summary, the members confirmed thatASC Union helped them to improve their activities and income, where 87 out of 100farmers confirmed that their income increased in the last 3 years, while 31 farmers out of100, respectively 8, 9 and 10 year-old-members, proclaimed that using the micro-loanhelped them to expand their activities, while 56 farmers confirmed that microcredithelped them not only in improving their income and activity, but also their productionincrement and activity expansion.